Serum Angptl2 and CyPA Levels in Acute Myocardial Infarction and In-Stent Restenosis After Percutaneous Coronary Intervention: A Single-Center Retrospective Case-Control Study - Zhou P; Yang T; Huang H; Tang F; Jin P; Zhou B (Vascular Health and Risk Management)
Pimo Zhou, Tai Yang, Hua Huang, Fang Tang, Peng Jin, Bo Zhou Department of Cardiovascular Medicine, Zhejiang Provincial People’s Hospital Bijie Hospital, Bijie City, Guizhou Province, People’s Republic of ChinaCorrespondence: Bo Zhou, Department of Cardiovascular Medicine, Zhejiang Provincial People’s Hospital Bijie Hospital, Bijie City, Guizhou Province, People’s Republic of China, Tel +86 18748588253, Email Zhouboo122@163.comPurpose: To explore the association between angiopoietin-like protein 2 (Angptl2) and cyclophilin A (CyPA) with acute myocardial infarction (AMI) and the occurrence of in-stent restenosis (ISR) after percutaneous coronary intervention (PCI).Patients and Methods: A single-center retrospective research was conducted. Clinical data from 146 AMI patients who underwent PCI at our hospital were analyzed and designated as the AMI group. Additionally, 56 healthy individuals who underwent medical check-ups during the same period were enrolled as the Control group. Serum levels of Angptl2 and CyPA were compared between the AMI and control groups. Furthermore, based on the presence or absence of in-stent restenosis (ISR) during the follow-up period, the AMI patients were further divided into ISR and NISR groups. Logistic regression analysis was utilized to ascertain the risk factors influencing ISR after PCI in AMI patients. The diagnostic value of serum Angptl2 and CyPA for ISR after PCI was assessed using the receiver operating characteristic (ROC) curve.Results: Compared with the Control group, the AMI group exhibited significantly elevated levels of Angptl2 and CyPA (P< 0.05). Logistic regression analysis identified serum Angptl2 and CyPA are risk factors for occurrence of ISR after PCI in AMI patients. Additionally, the ROC curve analysis demonstrated that the combined use of serum Angptl2 and CyPA achieved an area under the curve (AUC) of 0.895 for predicting ISR in AMI patients after PCI.Conclusion: Elevated serum levels of Angptl2 and CyPA in AMI patients who developed ISR after PCI suggest that these biomarkers may serve as potential risk indicators for predicting ISR following PCI.Keywords: angiopoietin-like protein 2, cyclophilin A, acute myocardial infarction, in-stent restenosis, percutaneous coronary intervention